Meretas Permasalahan Pendidikan di Indonesia - Priarti Megawanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
Education is the most important thing for every country to moving forward. Great country will put education as its first priority, because with education, the poverty of the people in the nation will change become prosperity. However, in the progress, education in Indonesia has to face several problems in every phase. Those problems only can solve with participations from all that contributors in education system, such as parent, teachers, headmasters, societies, and also the student themselves. In input phase, parent have big contribute to introduce good values to their children. Parent have big responsible to educate their kids with leadership values, so that they have enough preparation to become a early birth leader when they get into formal institution, which is school. In process phase, the parent with headmaster and teachers, together reinforce the student to live commonly with good values of leadership through organization culture in the school. Finally, in output phase, the student have to face so many challenge in reality world. The student that already passed previous phase with good values will grow become a great leader for this country.